EDUKASI PARENTING TERHADAP KAUM MARGINAL KOTA - Firda Mustika Mega (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2020)
Trough of a social perspective, the portrait of a small family living in a marginal urban area with poor economic conditions forces its residents to work as scavengers, buskers and homeless people. This profession is not only done by parents, but they also involve their children to work on the streets. The weak economic situation of the family has an impact on the growth and development of their children and their right to appreciate education. However, the failure to fulfill the right to proper education for children because poverty can be anticipated by providing education and solutions in care. This happened in the residential area of Kampung Ledhok Timoho Jogjakarta where in-depth assessment and intervention had been carried out on the parenting role of parents. This research is a descriptive qualitative study using the phenomenological approach of Alfred Schutz which has the concept of because of motive and in order to motive into understand parenting education as family education as well as the motives behind and the hopes they want to achieve. As a result, with strong support and desire, the threat of unequal education for marginalized people is broken down and education does not always have to be balanced with high costs.